6 - African Culture and the Quest for Sustainable and Improved Indigenous Knowledge Production: Nigeria and South Africa in Perspective - Idowu, Harrison Adewale (Journal of Higher Education in Africa, 2022)
Culture is the way of life of a people. But Western culture has deprived Africa of most of its cultural practices and values. The jettisoning of the African way of life for a Western one has affected indigenous knowledge production. Beaming the light on South Africa and Nigeria, this article interrogates the impact of culture/African ways of knowing on indigenous knowledge production in Africa, and unravels how much Africa has been able to incorporate its culture in knowledge production systems amid the penetration and preponderance of alien culture. It relies on historical perspective and document analysis. The article finds that African ways of knowing have been largely eroded in Nigeria, and that South Africa fares better but still faces some challenges. This has negatively affected the quest for sustained and improved indigenous knowledge production, vis-à-vis finding lasting solutions to the peculiar political, economic and social problems in these countries. It concludes that if Nigeria and South Africa, and indeed the African continent, are to attain sustainable and improved indigenous knowledge production, they must preserve African ways of knowing, without which indigenous knowledge production will remain in the abyss.